Penyakit Skabies Berhubungan Dengan Personal Hygiene Masyarakat - Elma Mentaya; Noraida Noraida; Abdul Khair (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2020)
Based on the Hulu Sungai Tengah District Health Office report, scabies continues to exist and is a problem that must to resolved immediately. The working area of the Pagat Health Center, which is one of the sub-districts in Hulu Sungai Tengah, experienced the highest increase in scabies cases. The purpose of this study was to determine personal hygiene relations include bathing habits and habit of using soap together with scabies in the working area of the Pagat Health Center. This type of research uses a retrospective approach (case-control study), which compares the behaviour of the sick group with a lively group associated with the incidence of scabies. The sample of this research is 30 people. Data will be analyzed using the x2 test (Chi-square). The results of this study indicate there is a relationship between bathing habits with the incidence of scabies P-value = 0.026